Mapping Solvation Dynamics at the Function Site of Flavodoxin in Three Redox States - Chang, Chih-Wei (2010)
Flavoproteins are unique redox coenzymes and the dynamic solvation at their function sites is critical to the understanding of their electron-transfer properties. Here, we report our complete characterization of the function-site solvation of holoflavodoxin in three redox states and of the binding-site solvation of apoflavodoxin. Using intrinsic flavin cofactor and tryptophan residue as the local optical probes with two site-specific mutations, we observed distinct ultrafast solvation dynamics at the function site in the three states and at the related recognition site of the cofactor, ranging from a few to hundreds of picoseconds. The initial ultrafast motion in 1–2.6 ps reflects the local water-network relaxation around the shallow, solvent-exposed function site. The second relaxation in 20–40 ps results from the coupled local water-protein fluctuation. The third dynamics in hundreds of picoseconds is from the intrinsic fluctuation of the loose loops flanking the cofactor at the function site. These solvation dynamics with different amplitudes well correlate with the redox states from the oxidized form, to the more rigid semiquinone and to the much looser hydroquinone. This observation of the redox control of local protein conformation plasticity and water network flexibility is significant and such an intimate relationship is essential to the biological function of interprotein electron transfer.